Economic Impact of Eurozone Sovereign Debt Crisis on Developing Asia - Minsoo Lee; Donghyun Park; Arnelyn Abdon; Gemma Estrada (Asian Development Bank (ADB), 2013)
The European Union (EU) has traditionally been an important economic partner for Asia. In addition to absorbing a significant share of the region's exports, the EU has been a major source of foreign direct investment and other capital flows into the region. In light of such close economic linkages between the EU and Asia, the euro crisis will undoubtedly influence Asia's short-term macroeconomic outlook. The key question, however, is how big the impact will be. This paper tries to answer this by examining both the trade and financial channels of crisis transmission. The impact on developing Asia will fall primarily on trade but there are also significant effects on the region's financial systems, especially its banking sector. However, overall, the magnitude of the shock from the euro crisis will be significantly smaller than the shock from the global crisis. A further cause for guarded optimism is that developing Asia still has relatively ample policy space to cushion a major external shock.
hdl:11540/2338
Keywords: E44; F15; F34; 330; euro crisis; developing Asia; financial channel; international trade; equity and bonds market; Öffentliche Schulden; Eurozone; Spillover-Effekt; Internationale Wirtschaftsbeziehungen; Schuldenkrise; Asien